2005
DOI: 10.1002/hbm.20184
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral activation of the prefrontal cortex after strategic semantic cognitive training

Abstract: The prefrontal cortex (PFC) has been implicated in the ability to apply semantic organizational strategies during verbal encoding and episodic learning. However, there has been no direct evidence demonstrating which specific areas in the PFC are engaged after cognitive training using semantic organizational strategies in healthy adult human subjects. In this study, we investigated the effects of semantic strategic training on brain activity and changes in behavioral performance, after cognitive training, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 33 publications
13
66
0
6
Order By: Relevance
“…In addition, participants recalled more words after the directed instructions for the SR condition and there was a significant correlation between semantic strategy scores and words recalled for the SR condition, a condition where this strategy can be used. These findings are similar to the ones found in healthy adult subjects 19 and other studies using different cognitive training in elderly subjects 21,22 and show that after a brief period of practice to apply efficient strategies older subjects can substantially improve their memory performance.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, participants recalled more words after the directed instructions for the SR condition and there was a significant correlation between semantic strategy scores and words recalled for the SR condition, a condition where this strategy can be used. These findings are similar to the ones found in healthy adult subjects 19 and other studies using different cognitive training in elderly subjects 21,22 and show that after a brief period of practice to apply efficient strategies older subjects can substantially improve their memory performance.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with studies of healthy older subjects employing longer periods of cognitive training showing increased activity after training in bilateral prefrontal regions including the inferior and medial frontal gyrus 21,23,25 . Previous results suggested that the left middle and inferior frontal gyrus and cerebellum support young adults' verbal encoding strategies 19,27 . In addition, there was greater activity in the right medial superior frontal gyrus and anterior cingulate.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…They proposed that the DLPFC was more directly involved in maintaining information relevant to response selection and execution at retrieval. Miotto et al (2006) investigated semantic organizational strategy application after cognitive training and found bilateral DLPFC and orbitofrontal cortex activation after training. It is difficult to evaluate the studies of Chan et al (2004) and Rodd et al (2005) against the requirements for working memory or semantic strategy application given that these tasks did not explicitly test for these effects.…”
Section: ")mentioning
confidence: 99%